2022
DOI: 10.3389/fsurg.2022.896542
|View full text |Cite
|
Sign up to set email alerts
|

An alternative asymmetric figure-of-eight single-layer suture technique for bowel anastomosis in an in vitro porcine model

Abstract: Anastomotic techniques are of vital importance in restoring gastrointestinal continuity after resection. An alternative asymmetric figure-of-eight single-layer suture anastomotic technique was introduced and its effects were evaluated in an in vitro porcine model. Twelve 15-cm grossly healthy small intestine segments from a porcine cadaver were harvested and randomly divided into asymmetric figure-of-eight single-layer suture (figure-of-eight suture) and single-layer interrupted suture technique (interrupted s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(9 citation statements)
references
References 46 publications
0
9
0
Order By: Relevance
“…Our results showed that the mean anastomosis time was significantly shortened in the asymmetric figure-of-eight single-layer suture technique group than in the single-layer interrupted sutures group, partly owing to the requirement of fewer knots (17). Time-saving is also important for patients who experience severe complications pre-or intraoperatively, such as intestinal volvulus and shock.…”
Section: Discussionmentioning
confidence: 79%
See 4 more Smart Citations
“…Our results showed that the mean anastomosis time was significantly shortened in the asymmetric figure-of-eight single-layer suture technique group than in the single-layer interrupted sutures group, partly owing to the requirement of fewer knots (17). Time-saving is also important for patients who experience severe complications pre-or intraoperatively, such as intestinal volvulus and shock.…”
Section: Discussionmentioning
confidence: 79%
“…Patients were divided into two groups: the single-layer asymmetric figure-of-eight suture technique group (group 1) and the traditional suture technique, i.e., single-layer interrupted sutures, group (group 2) ( 9 , 10 , 20 , 21 ). The single-layer asymmetric figure-of-eight suture technique has been described in detail by Liu et al ( 17 ). To summarize, an absorbable surgical suture (4–0 or 5–0 Ethicon) was used for anastomosis.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations